Efeitos tóxicos do uso abusivo de metilfenidato associado à cafeína - Freddo, Natália (2020)
Methylphenidate (MPH) is a psychostimulant widely prescribed for the Treatment of Attention Deficit Hyperactivity Disorder (ADHD), since it decreases motor restlessness and promotes increased concentration, attention and memory. However, due to its stimulating effects, MPH has been used as an easily accessible drug of abuse, cognitive enhancer and can be added in dietary supplements, along with other stimulants, the most prevalent being caffeine (CAF). The effects of this irregular and abusive use of MPH are not yet fully understood. The main objective of this work was to evaluate the toxic effects of MPH, used acutely and in non-therapeutic doses, isolated or associated with CAF, through behavioral tests, oxidative stress markers and parameters of the mitochondrial respiratory chain, using zebrafish as an animal model. Fish were exposed for 15 minutes to 3 different doses: MPH 80 (80 mg / L), CAF 150 (150 mg / L) and MPH80 + CAF150 (80 mg / L + 150 mg / L). After exposure, exploratory behavior, social preference and memory were evaluated. The following mechanisms related to the observed changes were investigated: oxidative stress markers (lipid peroxidation, non-protein thiols, protein carbonylation), nitric oxide generation, protein level and energy status parameters (activity of mitochondrial complexes I, II-III and IV). We demonstrated that MPH used in an abusive way promotes antisocial behavior and induces protein carbonylation. Regarding the oxidative effects, isolated MPH had a protective effect, inhibiting lipid peroxidation. CAF used alone promotes an increase in the activities of the mitochondrial respiratory complexes (II-III and IV) and the generation of nitric oxide. The association of MPH and CAF in the non-therapeutic context promotes anxiogenic behavior and memory impairment. Although this association decreases lipid peroxidation, it promotes an increase in protein carbonylation, in addition to an increase in the activities of mitochondrial respiratory complexes (II-III and IV). Our results show that the nontherapeutic exposure of MPH and CAF has relevant effects on sociability and anxiety behavior. The association impairs memory. Mechanisms related to these changes are related to protein lesion, as evidenced by increases in protein carbonylation, as well as increases in mitochondrial metabolism.